The Nose Knows: Review of Frank Rosell, Secrets of the Snout: The Dog’s Incredible Nose - Gordon, Joan (Humanimalia, 2020)
Frank Rosell. Secrets of the Snout: The Dog’s Incredible Nose. Chicago: U of Chicago P, 2018. xiii + 265 pp. $26 hc.